Colonization of therapeutic contact lens by dematiaceous fungi. Issue 4 (August 2019) - Radhakrishnan, Naveen; Panigrahi, Arun Kumar; Balasubramanium, Ashwin; Das, Manoranjan; Prajna, N Venkatesh
Highlights: Two patients with colonization of therapeutic contact lens with dematiaceous fungi without corneal involvement. The first patient with retained contact lens on the cornea for a prolonged period of time with fungal colonization. Abstract: Purpose: To report 2 patients with colonization of therapeutic contact lens with dematiaceous fungi. Methods: Case report. Results: The first patient had a retained soft contact lens on an opaque cornea for 4 years with brownish black multiple colonies on the soft contact lens and culture grew Bipolaris spp. The second patient was on therapeutic contact lens for pseudophakic bullous keratopathy for 4 months and developed a brownish colonization of contact lens with unidentified dematiaceous fungi. Both the patients had conjunctivitis but did not develop fungal keratitis. Conclusion: Judicious use of therapeutic contact lens is required in agrarian countries with adequate emphasis on strict adherence to the standard protocols and frequent replacement of the lens.